The Influence of Name Sounds in the Congressional Elections of 2006 - Grant W. Smith (Names, 2007)
Abstract This study retests this investigator's analytical model used in previously published studies of 1996 and 1998 elections measuring the influence of selected phonetic features of surnames on the relative success of various political candidates. The model presumably works best when voters are least motivated or most confused by issues. In the analyses of the 1998 elections the reliability of the model was 66%. In the analyses of the 2006 elections the reliability of the model was 68.6%. These results suggest that the analytical model is reliable over time and that the importance of issues and/or other factors was relatively constant or evenly polarized.